Chapter 5.33 The Profession of Research Management and Administration in Ireland - John Donovan; Susie Cullinane; Doris Alexander; Peter Scott; Jean van Sinderen Law (Emerald Publishing Limited, 2023)
The Government of Ireland, through the Department of Further and Higher Education, Research, Innovation and Science (DoFHERIS), sets the framework for the national research ecosystem. Within that ecosystem, the Research Management and Administrators (RMA) community evolved in response to changing circumstances and continues to evolve becoming a more professional and expert community. The profile of the community, admittedly based on a small sampling, is normal with a hint that females occupy the most senior roles. Most Irish research-performing organisations (RPOs) including the HE sector, College and State Research Organisations (CSRO), and the Health Service have RMA members active in The European Association of Research Managers and Administrators (EARMA). The next step in the profession's evolution in Ireland has to be the development of a single, national, and inclusive RMA network providing a representative voice for the profession with respect to issues such as career development and career paths.
10.1108/978-1-80382-701-820231067; 10.1108/978-1-80382-701-820231067; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262